Prediction of overall survival after re-irradiation with stereotactic body radiation therapy for pancreatic cancer with a novel prognostic model (the SCAD score). Issue 2 (November 2018) - Zhu, Xiaofei; Li, Fuqi; Ju, Xiaoping; Shen, Yuxin; Cao, Yangsen; Cao, Fei; Fang, Fang; Qing, Shuiwang; Jia, Zhen; Zhang, Huojun
Highlights: This study focuses on the re-irradiation for pancreatic cancer, which is rarely investigated, yet an important treatment option for recurrence of pancreatic cancer. Besides, it is the largest series of two courses of stereotactic body radiation therapy for pancreatic cancer. To the best of our knowledge, a novel prognostic score was firstly developed for selecting patients amenable to re-irradiation for pancreatic cancer. This scoring system may provide insights for individualized treatment. Abstract: Purpose: To develop a predictive model for stratification of patients with pancreatic cancer who may achieve survival benefits from re-irradiation with stereotactic body radiation therapy (SBRT). Methods: The score was developed based on clinical predictors of OS in 31 patients receiving two courses of SBRT with Cox proportional hazards model. Results were then validated in another cohort with 11 participants to assess the performance of the score. Results: In the training cohort, the median BED10 of the first and second SBRT was 59.5 Gy (48–85.5 Gy) and 50.2 Gy (43.7–66.9 Gy) in 5–8 fractions, while in the validation cohort, the median BED10 of the first and second SBRT was 59.5 Gy (52.5–66.9 Gy) and 47.7 Gy (40.6–54.8 Gy) in 5–8 fractions. The interval between the first and second SBRT of the training cohort and validation cohort was 10.5 months (6.1–24.3 months) and 12.8 months (6.5–29.1 months), respectively. Multivariable analysis showed that tumor stage ( P = 0.005), BED10 ( P = 0.006) and CA19-9 response ( P = 0.04) were significantly predictive of overall survival, which formed SCAD score (named after the initials of factors). Patients with the score < 3 points had a superior OS compared with those with the score ≥ 3 points in the validation cohort (median OS has not been reached vs. 15.9 months, P = 0.032). Conclusions: The SCAD score may have the potential to identify individuals benefiting from re-SBRT and be a step toward more personalized medicine.